Sistem Informasi Web MVC Penjualan Produk Desain Grafis pada Beastmedia Studio - Yanuar, Ghulam Ammar; Kristiyanto, Daniel Yeri (MEANS (Media Informasi Analisa dan Sistem), 2022)
Beastmedia Studio is a graphic design team that operates on the Fiverr platform, offering design services such as clothing design, logos, cartoon illustrations, and others. The freelancer team certainly really needs a website to accommodate their works so that other designers can see and have the opportunity to generate better income. The aspect of life that is heavily influenced by Information and Communication Technology is in the field of selling digital products. Product sales allow users who are looking for design products to make transactions on the web. Seeing the prospect of selling digital products, causing many graphic designers and freelancers to be interested in doing business in selling web-based graphic design products. Web Houses Graphics is a website selling design products based on Codeigniter 4 as an inspiration for designers and consumers to make their work easier. The development used is the Software Development Life Cycle (SDLC) method and testing through the Blackbox Testing method. Codeigniter 4 is an open source application with a basic PHP framework or hypertext preprocessor that uses the MVC method, namely models, views and controllers to create dynamic websites and uses the PHP language. Dynamic website is a type of web page that is organized based on content and layout that has a lot of information. Dynamic web has complex functionality such as validation of low latency input, progress reports, dynamic menus, and providing user experience on a website. Houses Graphics also provides vector designs such as types of vector illustration designs, logos, lettering, and others. Houses Graphics sees business potential in this digital era and sees consumer needs for graphic design. Consumers who need a design or design label, to meet the needs of these consumers. Houses Graphics requires a means that can bridge communication with consumers. Sales of graphic design products based on Codeigniter 4 using a responsive concept using PHP basics with an MVC framework and dynamic concepts using Bootstrap 5. Codeigniter 4 facilitates website development with complete features and the execution process is faster, so that in designing the mvc web information system sales of graphic design products are able to implemented using the Codeigniter 4 framework.